10.1142/9789814343060 (CrossRef Listing of Deleted DOIs, 2000)
Berberine (BBR), the core alkaloid of the traditional Chinese medicine Coptis chinensis (Huanglian), exhibits a notable pharmacological paradox: it possesses an oral bioavailability of less than 1% yet exerts broad therapeutic effects across the full spectrum of liver diseases, from metabolic dysfunction-associated steatotic liver disease (MASLD) through fibrosis to hepatic malignancies. This review constructs an integrated mechanistic framework to interpret BBR's holistic pharmacological characteristics, which distinguish it from conventional single-target drugs. In MASLD, BBR engages a convergent AMPK-SIRT-Nrf2 network to ameliorate insulin resistance, lipid dysregulation, oxidative stress, and hepatic inflammation. Combined with the complementary actions of its bioactive metabolites, it achieves parent-metabolite coordinated efficacy that embodies the holistic principle of traditional Chinese medicine. In liver fibrosis, BBR may block hepatic stellate cell activation via the TGF-β1/Smad3 pathway and eliminate activated HSCs through multiple programmed cell death pathways, particularly ferroptosis, which may overcome apoptosis resistance. In hepatic malignancies, BBR suppresses tumor progression, metastasis, and chemoresistance via apoptotic, ferroptotic, and immunomodulatory mechanisms. Current clinical evidence validates its metabolic benefits in MASLD, whereas clinical data regarding fibrosis and hepatic malignancies remain insufficient. Improving its poor bioavailability through structural modification and nanocarrier delivery is critical for clinical translation. This review provides a modern pharmacological rationale for the clinical application of Coptis chinensis-based formulas against progressive liver diseases.